Assessment of the Connection Between Blue Light and Anxiety: A System Biology Approach: Assessment of the connection between blue light and anxiety - Rezaei-Tavirani, Mostafa; Arjmand, Babak; Razzaghi, Zahra; Robati, Reza M (Journal of Lasers in Medical Sciences, 2025)
Introduction: Blue light with therapeutic properties is the high-energy part of the visible light spectrum with various biological effects. The main aim of this study is to elucidate blue light exposure and anxiety via protein-protein interaction (PPI) network analysis. Methods: Anxiety-related genes were extracted from the GeneCards database and assessed via gene clustering and PPI network analysis to identify the hub genes. Blue light-targeted genes in 3D skin were revealed from the Gene Expression Omnibus (GEO) database, and the significant differentially expressed genes (DEGs) were identified. The significant DEGs were searched among the hub genes. The common significant DEGs and the hub genes, together with their first neighbors, were determined and discussed. Results: A total number of 56 significant DEGs were pointed out as the targets of blue light. Among the 10696 anxiety-related genes, 772 individuals were selected as top genes and evaluated via PPI network analysis. IL6 appeared as the common gene between the significant DEGs and the 55 hub genes of the PPI network. Twelve genes were pointed out as the first neighbors of IL6. GIFtS analysis showed that Il6, H3-5, PFN1, DEFB103A, HMGB1, and RPLP1 were genes related to anxiety and were targeted by blue light. Conclusion: In conclusion, six targeted genes by blue light were related to anxiety. Downregulation of IL6 appeared as a factor in improving anxiety. However, the first neighbors of IL6 were not consistent with the role of IL6 in the decrement of anxiety.